Construction of (3, 6)-connected polyoxometalate-based metal–organic frameworks (POMOFs) from triangular carboxylate and dimerized Zn4-ε-Keggin. Issue 41 (11th October 2017) - Dong, Bao-Xia; Chen, Hua-Bo; Wu, Yi-Chen; Zhao, Juan; Teng, Yun-Lei; Liu, Wen-Long; Li, Zong-Wei
Abstract : The methodology of extension of reduced transition metal-grafted ε-Keggin polyoxoanions with two types of terphenyl-based tricarboxylates was used to isolate two (3, 6)-connected 3D POMOFs. Abstract : Using the methodology of extension of reduced transition metal-grafted ε-Keggin polyoxoanions with two types of terphenyl-based tricarboxylates of H3 L 1 (3, 5′, 3′′-position substitution) and H3 L 2 (4, 5′, 4′′-position substitution) we isolated two (3, 6)-connected 3D polyoxometalate-based metal–organic frameworks, [TBA]3 [H3 PMo12 O40 ][Zn4 L 2 ] (1, YZU-105 ), and [TPA]3 [H3 PMo12 O40 ][Zn4 L 1 ]·0.5H2 O (2, YZU-106 ) (H3 L 1 = [1, 1′;3′, 1′′-terphenyl]-3, 5′, 3′′-tricarboxylic acid; H3 L 2 = [1, 1′;3′, 1′′-terphenyl]-4, 5′, 4′′-tricarboxylic acid; TBA = tetrabutylammonium; TPA = tetrapropylammonium). In both compounds, the building block was the dimerized form of Zn4 -{ε-H3 PMo12 O40 }. Such dimerization left six anchoring points for each dimer and, as a result, a 6-connected node was formed. Compounds1 and2 exhibited topologies of (4·8 5 )3 (4·8 2 )6 and (6 5 ·10)3 (6 3 )6, respectively. This work illustrates that use of tri-carboxylate substitutions in different positions (3, 5′, 3′′-position/4, 5′, 4′′-position) in tripodal terphenyl-based ligands allows different extents of twisting of the peripheral aromatic ring with respect to the central ring, thereby giving rise to different extending directions and symmetries.